Participation by or for design? The case of Albion Square in post-earthquake Ōtautahi Christchurch. Issue 2 (4th May 2019) - Hoddinott, Wendy; Swaffield, Simon; Stewart, Emma J.
Abstract: The quality of public space is integral to liveable cities, which also require empowered communities. This article is focused on the participatory design process of Albion Square, in Ōhinehou Lyttelton, which takes place in postearthquake Ōtautahi Christchurch, Aotearoa New Zealand. We ask: How do interactions between landscape architectural design expertise and statutory public participation processes shape the design of public space? The analysis uses two theoretical perspectives: types of design process, and approaches to public engagement. Based on interviews, site observation and documentary analysis, findings reveal that institutional processes in Aotearoa New Zealand can inhibit relationships between community and designers, resulting in suboptimal design outcomes. More direct engagement between designers and community through codesign is proposed to improve the quality of the design of public space. We raise research questions regarding tensions between design expertise and statutory process and identify an opportunity to revitalize 'elegance' as a conceptual response to these imperatives.